Identification of Zoophilic Dermatophytes Using MALDI-TOF Mass Spectrometry - Baumbach, Christina-Marie; Müller, Stefanie; Reuschel, Maximilian; Uhrlaß, Silke; Nenoff, Pietro; Baums, Christoph Georg; Schrödl, Wieland (Frontiers in Cellular and Infection Microbiology, 2021)
Dermatophytoses represent a major health burden in animals and man. Zoophilic dermatophytes usually show a high specificity to their original animal host but a zoonotic transmission is increasingly recorded. In humans, these infections elicit highly inflammatory skin lesions requiring prolonged therapy even in the immunocompetent patient. The correct identification of the causative agent is often crucial to initiate a targeted and effective therapy. To that end, matrix assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) represents a promising tool. The objective of this study was to evaluate the reliability of species identification of zoophilic dermatophytes using MALDI-TOF MS. The investigation of isolates from veterinary clinical samples suspicious of dermatophytoses suggests a good MALDI-TOF MS based identification of the most common zoophilic dermatophyte Microsporum canis. Trichophyton (T.) spp. usually achieved scores only around the cutoff value for secure species identification because of a small number of reference spectra. Moreover, these results need to be interpreted with caution due to the close taxonomic relationship of dermatophytes being reflected in very similar spectra. In our study, the analysis of 50 clinical samples of hedgehogs revealed no correct identification using the provided databases, nor for zoophilic neither for geophilic causative agents. After DNA sequencing, adaptation of sample processing and an individual extension of the in-house database, acceptable identification scores were achieved (T. erinacei and Arthroderma spp., respectively). A score-oriented distance dendrogram revealed clustering of geophilic isolates of four different species of the genus Arthroderma and underlined the close relationship of the important zoophilic agents T. erinacei, T. verrucosum and T. benhamiae by forming a subclade within a larger cluster including different dermatophytes. Taken together, MALDI-TOF-MS proofed suitable for the identification of zoophilic dermatophytes provided fresh cultures are used and the reference library was previously extended with spectra of laboratory-relevant species. Performing independent molecular methods, such as sequencing, is strongly recommended to substantiate the findings from morphologic and MALDI-TOF MS analyses, especially for uncommon causative agents.